Some biological active components of conus quercinus venom - Abogadie, Fe
Acetic acid extract of the crude venom from the vermivorous snail Conus quercinus was resolved into 7 chromatographic peaks by gel permeation chromatography. All peaks were found active when injected intracerebrally into mice. Peak II, when ran in the HPLC, was further resolved into at least 40 peaks. Major peaks from this run were bioassayed by intracerebral injection into mice and many of them were found active. From the same run, three peptides which act on the vertebrate central nervous system were purified to homogeneity by a series of HPLC runs. Two of these peptides are homologous to each other while the third one contains one residue of ﻻ-carboxyglutamic acid. When injected intracerebrally into mice, these peptides elicit a type of activity similar to that elicited by conopressin GI. The symptomatology includes grooming and scratching.